MODEL PROBLEM BASED LEARNING BERBANTU CHATGPT TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V SD - Afzalur Rachmah, Elfa Aulia; Arif Mahya Fanny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of implementing the ChatGPT-assisted Problem Based Learning (PBL) model on students’ critical thinking skills in Pancasila Education learning on cultural diversity material in Grade V of elementary school. The background of this study is based on students’ low critical thinking skills, the lack of variation in innovative learning models, and the minimal use of artificial intelligence (AI)-based technology to support learning. The research employed a Quasi-Experimental Design with a Posttest-Only Control Design to measure students’ critical thinking skills. The research subjects consisted of two classes: Class VA (25 students) as the experimental group, which received instruction using the ChatGPT-assisted PBL model, and Class VB (25 students) as the control group, which received conventional learning. The test was administered once (posttest) after the implementation of the learning model to determine students’ final critical thinking skills in each class. The experimental group was taught using the Problem Based Learning (PBL) model assisted by the ChatGPT platform, while the control group was taught using the Problem Based Learning model without ChatGPT assistance. Posttest data were used to compare critical thinking skills between the two groups and to determine the effect of the ChatGPT-assisted PBL model on students’ critical thinking skills at Grade V of UPT SD 145 Gresik. Data analysis was conducted using normality tests, homogeneity tests, and an independent samples t-test with the assistance of SPSS software. The results showed a significant difference between the experimental and control groups. Based on the findings, it can be concluded that the ChatGPT-assisted Problem Based Learning (PBL) model has a significant effect on students’ critical thinking skills in Pancasila Education learning on cultural diversity material in Grade V of UPT SD 145 Gresik. The analysis results indicated a Sig. (2-tailed) value of < 0.001; therefore, H₀ was rejected and H₁ was accepted.